It couldn't just happen : knowing the truth about God's awesome creation - Richards, Larry, 1931- (Nashville : Tommy Nelson, 2011)
Presents Biblical and scientific evidence that the natural world was created by God rather than through evolution.
Originally published: Dallas : Word Pub., c1989.
Includes bibliographical references (p. 235-236) and index.
Keywords: Creation -- Juvenile literature; Evolution -- Religious aspects -- Christianity -- Juvenile literature; Creationism -- Juvenile literature